Asset Forfeiture for the Offense of Illicit Enrichment: Between Eradication and Deterrence - Ashalirrohman, Yusron; Nurhayati (Lex Journal: Kajian Hukum & Keadilan, 2024)
The Indonesian government has ratified the United Nations Convention Against Corruption (UNCAC) or the UN Anti-Corruption Convention with law number 7 of 2006. One of the important issues is the return of criminal assets through asset confiscation and criminalizing illicit enrichment. However, to date the Asset Forfeiture Bill has not been passed. This research aims to examine the practice of asset confiscation in Indonesia, the obstacles that arise as a result of the incomplete discussion of the Draft Law on Asset Forfeiture, giving the impression that there is an attempt to obstruct it, and the urgency of reforming the law for handling criminal acts of corruption by criminalizing asset confiscation for illicit enrichment offenses. This research uses a normative method with a statutory, conceptual and country comparison approach. From the results of this research, recommendations were obtained to strengthen and encourage efforts to ratify the Draft Law on Asset Forfeiture in Indonesia.